Handling anger and frustration - Cambridge Educational (New York : Cambridge Educational, 2011)
This video examines the problems arising from extreme or repressed anger and presents helpful methods for loosening the grip that all-consuming rage can have on one's mind and actions. Viewers learn basic psychological concepts relating to the human need to confront and remove obstacles, a primal instinct that all too easily translates into'lashing out.' Encouraging students to look closely at their feelings in these trigger situations, the program highlights steps that can be taken toward dealing rationally with anger sources, focusing on staying'centered' rather than'getting even.' Family and peer relationships, the importance of self-respect and respect for others, and useful distinctions between'good' and'bad' anger all come into play here.
DVD format
Keywords: Anger; Frustration